Developmental odontogenic cysts with special focus on the occurrence of multiple cysts and syndromic association: a single-centre cross-sectional study from the Czech Republic - Szaraz, David; Ksinan, Albert J; Machacek, Ctirad; Borilova Linhartova, Petra (Orphanet journal of rare diseases, 2025)
BACKGROUND: This retrospective study aims to evaluate the relative representation of individual types of developmental odontogenic cysts (DOCs), especially from the perspective of syndromic and non-syndromic multiple DOCs in the Czech population. In addition, we also summarize the previous studies on the occurrence of multiple DOCs and provide a literature review of case reports and case series on non-syndromic multiple DOCs, particularly dentigerous cysts (DCs) and odontogenic keratocysts (OKCs). METHODS: The study included histologically confirmed DOCs retrieved between January 1, 2012, and August 8, 2023, at the Clinic of Maxillofacial Surgery, University Hospital Brno, Czech Republic. All specimens were re-classified according to the fifth edition of the World Health Organization Classification of Head and Neck Tumors, 2022. Patients with an uncertain histological diagnosis were excluded from the study. RESULTS: Of a total of 377 patients, 286 had DCs, 85 OKCs, 5 orthokeratinizing odontogenic cysts (OOCs), 1 botryoid cyst, and 1 calcifying odontogenic cyst. The proportion of patients with multiple DCs in our study (6.6%) was higher than usually reported in the literature. The study also found that 100% of patients with multiple DCs did not exhibit any syndromic associations. On the other hand, 66% of multiple OKCs were associated with the Naevoid Basal Cell Carcinoma Syndrome (NBCCS) and the proportion of OKC patients with NBCCS (7%) was relatively higher than in other studies. Recurrence of OKCs was also significantly associated with NBCCS (p < 0.05). Only one patient presented with bilateral OOCs, without any association with a syndrome. CONCLUSION: Multiple OKCs are more likely to develop in syndromic patients, while none of the multiple DCs were associated with a syndrome. The incidence of multiple OOCs and other DOCs is extremely rare. Still, we conclude that patients with multiple DOCs should be carefully considered for examination by other specialists to rule out possible syndromic involvement.
Keywords: senioři; Synchronous; Cross-Sectional Studies; Gorlin-Goltz syndrome; Odontogenic keratocyst; Retrospective Studies; Odontogenic Cysts; Developmental odontogenic cyst; mladiství; Česká republika; Dentigerous cyst; Multiple cysts; Middle Aged; mužské pohlaví; dentigerózní cysta; průřezové studie; Adult; mladý dospělý; Czech Republic; dítě; odontogenní cysty; Child; Child, Preschool; Young Adult; Non-syndromic; ženské pohlaví; Dentigerous Cyst; retrospektivní studie; předškolní dítě; Humans; NBCCS; Orthokeratinizing odontogenic cyst; lidé středního věku; Syndromic; dospělí; Female; Aged; Adolescent; lidé; Male